ANALISIS PERUBAHAN KEPADATAN ZOOPLANKTON BERDASARKAN KELIMPAHAN FITOPLANKTON PADA BERBAGAI WAKTU DAN KEDALAMAN DI PERAIRAN PULAU BADI KABUPATEN PANGKEP - Tambaru, Rahmadi; Muhiddin, Amir Hamzah; Malida, Hasrul Suaidi (Torani Journal of Fisheries and Marine Science, 2014)
Basic of zoooplankton dependence on the phytoplankton to fulfill the requirement energy needs and creates acomplex relationship. The relationship of dependency between fitoplankton and zooplankton are very close,eventually can cause the changing in the zooplankton density in the time and space. The aims of study toaanalyze the changes in the zooplankton density on the phytoplankton abundance based on various time anddepth in the waters Badi Island of Pangkep Regency. The research has been carried out December 2009 toApril 2010. The results showed that changes in zooplankton density, not only because of the phytoplanktonabundance but also due to other factors such as sunlight. Keywords : density, abundance, zooplankton, phytoplankton, Badi Island